Complicaciones derivadas de accidente ofídico en pacientes que ingresan por esta causa al Hospital General Puyo, Puyo año 2015 - Jaramillo Arboleda, Valeria Tamara (2015)
The purpose of the research was to identify the complications of snake bites in 40 people who joined this cause to the General Hospital Puyo to reduce risk factors. The design was cross-sectional, descriptive, bibliographic and field. Instruments for each target set as a guide for observation and survey to collect information was given. It was obtained as a result that snakebite occurs frequently in people over 30 years with 70%; male with 75%; Shuar is the most susceptible to snake bites with 80%, patients living in rural areas and represent 100% of the accidents. Incomplete primary education prevails in 95%. The labor activity that prevails and is engaged in agriculture with 90%; snakebite occurs most frequently in hands and feet with 37.50%; Complications secondary infection is persisting in the area of the bite with 66.67%; among the predisposing factors include applying tourniquet 12.50% and suck the wound and 17.50% for medical care takes more than an hour with 50%. It was concluded that manifested complication of snake bites is the secondary infection at the site of the bite and not applying proper care techniques, so it is important to decrease the incidence and complications resulting from snake bites through the action plan proposed through educational talks, workshops care, primary prevention and delivery of information material